SIKAP, PREFERENSI, DAN NIAT BELI TERHADAP PRODUK MAKANAN RINGAN PADA ANAK USIA SEKOLAH - Sumarwan, Ujang; Johan, Irni Rahmayani; Anindita, Dwi (Jurnal Ilmu Keluarga dan Konsumen, 2011)
This study aimed to analyze attitudes, preferences, and purchase intentions of snack products on school-age childrens; to analyze the correlation between research’s variables; and to analyze influence factor of purchase intentions on snack products. The study design was quasi experimental, which will have two treatments given to two groups, namely men's and women's groups. Two treatments were given to the sample was advertising exposure then consumers test (treatment 1), and consumer test then advertising exposure (treatment 2). The participants of this study were 60 students from sixth grade elementary school that were selected randomly. Base on treatment and sex, Independent Samples T Test showed that attitudes, preferences, and purchase intentions wasn’t different significantly. Spearman’s correlation analysis showed that attitudes had significant correlation with purchase intentations. Children purchase intentations was influenced by attitudes.